Muscle metabolome and adipose tissue mRNA expression of lipid metabolism-related genes in over-conditioned dairy cows differing in serum-metabotype - Hassan Sadri (Nature Portfolio, 2021)
Abstract Over-conditioned dairy cows, classified by body condition score (BCS) and backfat thickness (BFT) are less able to metabolically adapt to the rapidly increasing milk yield after parturition. Based on serum metabolome and cluster analyses, high BCS cows (HBCS) could be classified into metabotypes that are more similar to normal (NBCS) cows, i.e., HBCS predicted normal (HBCS-PN) than the HBCS predicted high (HBCS-PH) cows—similar to the concept of obese but metabolically healthy humans. Our objective was to compare muscle metabolome and mRNA abundance of genes related to lipogenesis and lipolysis in adipose tissue between HBCS-PH (n = 13), HBCS-PN (n = 6), and NBCS-PN (n = 15). Tail-head subcutaneous fat was biopsied on d −49, 3, 21, and 84 relative to parturition. Potential differences in the oxidative capacity of skeletal muscle were assessed by targeted metabolomics in M. semitendinosus from d 21. Besides characteristic changes with time, differences in the mRNA abundance were limited to lipogenesis-related genes on d −49 (HBCS-PH > HBCS-PN). The HBCS-PH had more than two-fold higher muscle concentrations of short (C2, C4-OH, C6-OH) and long-chain acylcarnitines (C16, C18, and C18:1) than HBCS-PN, indicating a greater oxidative capacity for fatty acids (and utilization of ketones) in muscle of HBCS-PN than HBCS-PH cows.